ВЕРБАЛІЗАТОРИ ДАВНЬОГЕРМАНСЬКИХ МАГІЧНИХ ТЕХНІК ПРИ ПРОРОКУВАННІ ДОЛІ - Троць, Олена Володимирівна (Studia Philologica, 2013)
The article deals with the analysis of Old Germanic magic in its correlation with the fate in the Old Germanic manuscripts on the basis of the linguocultural approach. Magic as described in the оld texts was represented by the following words: seiðr, spá (spae), galdr “witchcraft, incantation”, and was considered to be the province of women. Etymology of these lexemes proves the fact that there was a determined connection between the form and the meaning of the suggested lexemes. These magic techniques helped women-practitioners to foresee the fate, future events, or to cast a magic spell.